2014
DOI: 10.1007/s00590-014-1551-8
|View full text |Cite
|
Sign up to set email alerts
|

Trapezio-metacarpal arthrodesis: procedure and results

Abstract: The high prevalence of trapezio-metacarpal joint (TMJ) osteoarthritis leads to develop techniques to improve surgical outcomes when conservative treatment has failed. We have evaluated 18 patients with Eaton III TMJ osteoarthritis, who underwent an arthrodesis. Using a dorsal-radial curved shaped skin incision the TMJ was exposed through the space between the abductor pollicis longus and the extensor pollicis brevis muscles. The articular capsule was divided and the TMJ was opened. Neat curettage was then perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…As documented above, other techniques, such as the use of a single oblique lag screw or the use of T-plate fixation, resulted in nonunion rates between 6% and 26%. 3,16,18,22,23 We had had complete fusion of all 22 TMAs. It is possible that there is increased stability of the construct or possibly a compressive force of the oblique interfragmentary screw when added to the T-plate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As documented above, other techniques, such as the use of a single oblique lag screw or the use of T-plate fixation, resulted in nonunion rates between 6% and 26%. 3,16,18,22,23 We had had complete fusion of all 22 TMAs. It is possible that there is increased stability of the construct or possibly a compressive force of the oblique interfragmentary screw when added to the T-plate.…”
Section: Discussionmentioning
confidence: 99%
“…Another commonly used technique is a lag screw to provide interfragmentary compression and assist in bone fusion. Galan et al 22 studied the use of an oblique cannulated lag screw in TMAs with a distal radius bone graft. They found a 6% nonunion rate (1 of 18 patients).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, only two studies have demonstrated model-ing of the bone graft for arthrodesis of the trapeziometacarpal joint. Galan et al 18) harvested a cylinder-shaped bone graft from the distal radius and fitted this to the same defect made at the joint. After surgery, the affected thumb was immobilized for 6 weeks and 17 of 18 (94%) patients obtained bony union.…”
Section: Discussionmentioning
confidence: 99%